Physician–patient end-of-life care discussions: Correlates and associations with end-of-life care preferences of cancer patients—a cross-sectional survey study. (December 2014) - Tang, Siew Tzuh; Liu, Tsang-Wu; Liu, Li Ni; Chiu, Chang-Fang; Hsieh, Ruey-Kuen; Tsai, Chun-Ming
Background: Honoring patients' treatment preferences is a key component of high-quality end-of-life care. Connecting clinical practices to patients' preferences requires effective communication. However, few cancer patients reported discussing end-of-life-care preferences with their physicians. Aim: To identify correlates of physician–patient end-of-life-care discussions and to investigate associations of physician–patient end-of-life-care discussions with patient end-of-life-care preferences. Design: A cross-sectional survey from April 2011 through November 2012. Setting/participants: A convenience sample of 2467 cancer patients (89.3% participation rate) whose disease was diagnosed as terminal and unresponsive to current curative cancer treatment was recruited from 23 teaching hospitals throughout Taiwan. Results: Only 7.8% of respondents reported discussing end-of-life-care preferences with their physicians. Physicians were more likely to discuss end-of-life-care preferences with cancer patients who accurately understood their prognosis but less likely to do so if patients were married or received care in a hospital with an inpatient hospice unit. Furthermore, physician–patient end-of-life-care discussions were significantly, positively associated with the likelihood of preferring comfort-oriented care and hospice care, but negatively associated with preferences for receiving cardiopulmonary resuscitation when life is in danger and aggressive life-sustaining treatments at end of life, including intensive care unit admission, cardiac massage, intubation, and mechanical ventilation support. Conclusion: Physician–patient end-of-life-care discussions are correlated with accurate prognostic awareness, marital status, and institutional characteristics and negatively associated with terminally ill cancer patients' preferences for aggressive end-of-life care. Interventions should be developed to facilitate timely end-of-life-care discussions between at-risk patients and their physicians, thus honoring patients' end-of-life-care preferences and possibly avoiding futile life-sustaining treatments.